1998 St. Vincent and the Grenadines elections : post-election report - Payne, Douglas W. (Centre for strategic and International Studies WashingtonUS, 1998)
Highlights the events leading up to, the conduct of and the outcome of the 1998 St. Vincent and the Grenadines elections.